Unpacking Micro-Level Leadership Behaviours in Digital Transformation: A Qualitative Systematic Review of Behavioural Antecedents to Organisational Performance - Novrizal; Cahyatih Kumandang (LPPM STIE Kasih Bangsa, 2026)
Digital transformation has intensified scholarly interest in leadership; however, existing research predominantly emphasises leadership styles and strategic orientations, leaving the role of micro-level leadership behaviours underexplored. This qualitative systematic literature review synthesises prior studies to examine how everyday leadership behaviours function as behavioural antecedents of organisational performance in digital transformation contexts. Drawing on a structured review of interdisciplinary literature, the study identifies cognitive, relational, and adaptive leadership behaviours as central mechanisms through which digital initiatives are translated into performance outcomes. The findings reveal that micro-level behaviours—such as sensemaking, empowering communication, psychological safety cultivation, and behavioural flexibility—indirectly shape organisational performance by fostering digital capabilities, innovative work behaviour, and employee resilience. By shifting the analytical focus from abstract leadership constructs to observable behavioural micro-foundations, this review contributes to digital leadership and organisational performance literature and offers integrative insights for future empirical research and managerial practice